(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The human gene encoding the QRFP receptor (nomenclature as agreed by the NC-IUPHAR Subcommittee on the QRFP receptor [16]; QRFPR, formerly known as the Peptide P518 receptor), previously designated as an orphan GPCR receptor was identified in 2001 by Lee et al. from a hypothalamus cDNA library [15]. However, the reported cDNA (AF411117) is a chimera with bases 1-127 derived from chromosome 1 and bases 155-1368 derived from chromosome 4. When corrected, QRFPR (also referred to as SP9155 or AQ27) encodes a 431 amino acid protein that shares sequence similarities in the transmembrane spanning regions with other peptide receptors. These include neuropeptide FF2 (38%), neuropeptide Y2 (37%) and galanin Gal1 (35%) receptors.